Capacity Building for Community Organizations in Maintaining Public Safety and Order in The Kudus Police District: A Study of The Partnership Between The Community Relations Unit and The Lindu Aji Community Organization - Ronni Bonnic; Surya Nita; Genoveva Ambar Wulan (International Journal Labs, 2026)
Public security and order (kamtibmas) are fundamental for social stability and sustainable development, yet traditional policing alone is often insufficient to address complex social dynamics. This study aims to examine the effectiveness of capacity building and strategic partnerships between the Kudus Police Community Development Unit (Satuan Pembinaan Masyarakat/Satbinmas) and the Lindu Aji Community Organization in enhancing community-based security. Employing a qualitative case study design, data were collected through in-depth interviews, observations, and document analysis, focusing on the interaction patterns, trust, social networks, and normative values within the CSO-police partnership. The findings indicate that while the coaching and partnership initiatives have contributed to building social capital, including trust, networks, and norms, the approach remains largely administrative and reactive, limiting the proactive engagement of CSOs in early detection and conflict prevention. Intensive communication and operational synergy between Satbinmas and Lindu Aji demonstrate potential for collaborative security governance, yet the absence of structured operational frameworks, standard operating procedures, and role clarity restricts the effectiveness of these partnerships. The study concludes that transforming CSOs into active, adaptive agents requires participatory, structured coaching and institutionalized strategic partnerships, enabling sustainable kamtibmas. The results provide both theoretical insights on social capital-driven policing and practical guidance for optimizing community-police collaboration to strengthen public safety.